Cultural Functions and Values in the Ritual of Taking Fire in Kayangan Api Bojonegoro - Bafana, Abdul Faiq; Rizal, Maulfi Syaiful (Universitas Negeri Semarang, 2025)
Bojonegoro, as one of the regions in East Java, has a unique tradition, the ritual of taking fire, which is usually carried out when there is a big event in Bojonegoro City. This study aims to analyze the function and cultural value of the ritual of taking fire in Kayangan Api for the people of Bojonegoro. The function theory of William R. Bascom explains that literature has several functional values, namely, as a form of entertainment, a tool for the ratification of cultural institutions and institutions, education, and a tool of coercion. As well as Koentjaraningrat Value Theory. The method used in this study is qualitative descriptive. The data collection techniques used were observation, interviews with key players, documentation, and notes during the event. This research shows that Kayangan Api, as a tourist attraction, has an entertainment function and social value in its story. Taking a fire is a tradition in Bojonegoro and a way to show local art. The stages of the procession of taking the fire start from the slametan the day before the taking of the fire and the taking of the fire by the locksmith, which is then relayed from the locksmith to the sub-district head which will later be given to the torch-carrying team to the pavilion in the square. Some values can be taken from the procession of taking the fire, namely social values that can be seen from the cooperation between the management of the fire garden and the culture and tourism office of the city of Bojonegoro who work together to prepare the event and from the story of the fire garden itself, besides that there are religious values found in the implementation of slametan as a form of gratitude and asking for safety during the event.